A Zooarchaeological Study of Fishing Strategies Over Time at the Rio Chico Site on the Central Coast of Ecuador - (:unkn) unknown (My University, 2018)
Human response to environmental crises is an issue we face today and will continue to face in the future. Food security, in the sense of access to sufficient nutrition, is a part of that. Ocean fisheries are among the critical resources affected. The archaeological record can provide insights into ecological strategies that did – or did not - work. Archaeological evidence of human occupation on the Ecuadorian coast stretches back 11,000 years, making this region of South America well-suited to evaluating ecological resilience and sustainability; however, detailed analyses of prehistoric fish remains from coastal Ecuador are rare. This thesis concerns prehistoric marine fishing strategies practiced along the coast of Ecuador and the impacts of environmental and cultural changes on human ecology. Archaeological evidence for which fishing strategies show ecological resilience and sustainability over time will be analyzed to evaluate approaches to food security over a span of 5000 years.
Keywords: archaeology; Ecuador; fishing strategies; Manteño; Valdivia; zooarchaeology